Study on the Middle East Cancer Consortium (MECC) - A Beacon of Human Decency - R. J. Lazarovitch-Wiles; M. Silberman (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
We are facing an escalating global health problem, whereby the suffering from cancer-related illnesses is vastly increasing. It is more than a medical crisis: as cancer knows no geographical, cultural or religious boundaries, it is a human, economic and social issue. This global crisis has given us an opportunity to overcome our modern culture of individualistic isolation and to begin learning how to help ourselves by helping others, by opening ourselves to a shared language of compassion and hope.1 Healthcare professionals (and especially, nurses) are well-positioned to promote better communication skills, mutual respect and, perhaps eventually, peace. The Middle East Cancer Consortium (MECC) exemplifies a living model for promoting open communication and sharing of information in times of strife. Our approach is to bring together oncology nurses from diverse religions, ethnic backgrounds and different communities throughout the Middle East, with a common goal to implement, expand and improve palliative care programs in the region. We learned that suffering may become a shared language, as very few of us would refuse to alleviate a dying enemy’s suffering. Central to MECC gatherings are sessions where nurses learn from each other about how to communicate with patients and their families as well as how to convey empathy. The personal story recounted here reveals that the powers of science and medicine go hand-in-hand with the capacity for empathy and trust. Utilizing this approach, MECC participants have successfully ventured into the hostile territories of prejudice, politics and ideology.